Sovereignity Issues and Legal Framework Challenges for Foreign Direct Investment in Developing Countries - Keita, Kain; Yeon, Asmah Laili Binti; Razak, Aida Binti Abdul; Abdullah, Nor Anita (NAJAHA, 2023)
A host state has faced sovereignty issues and challenges in adopting and applying a legal framework for Foreign Direct Investment (FDI) governed by International Investment Law (IIL). IIL provides certain protection to FDI in a host country. The protections have been considered standard in the liberation of the FDI, which could positively impact the FDI attraction into countries. However, the host state's ability to regulate the public interests for a common concern of the peoples, such as social, economic, environmental, and human rights achievement, is indeterminate in IIL, and it became mostly a challenge for the host states. These needs are increasingly being requested by the population from governments. This study looks at how the state’s sovereignty power can be met in the adoption and application of laws and policies for the public's interest and assessment methods which are mostly used by the court in foreign investment disputes. An empirical analysis of the legal issue based on available literature is made. The findings of this study show that the necessity to understand the fears for sovereignty underpins the debate on its legitimacy in investment arbitration. The established sovereignty of state laws is shown in FDI and the desired areas of public interest regularisation. The international arbitral tribunals may reveal the right to balance between private and public interests in applying the national laws, which significantly show unclear and or open-textured international investment agreements (IIAs) provisions. The public interests are mostly applied to national laws over international law.